Hyperbilirubinemia has Predictive Potential for the Diagnosis of Appendiceal Perforation - Madeeha Shahid, Muhammad Khalid, Aun Ali, Nadia Shahid, Jabbar Ahmed Qureshi, Zenab Noorain, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute appendicitis is an inflammation of the vermiform appendix. Usually, the diagnosis is made on clinical evaluation and elevated leukocyte count (TLC). But in cases when the clinical diagnosis is indeterminate, additional assessment needs imaging. Despite the increased use of modern diagnostic modalities such as Sonography, computed tomography (CT), and diagnostic laparoscopy, the frequency of misdiagnosis of appendicitis has remained constant (15%) as has the rate of appendiceal rupture. Presently, some serum markers such as C-reactive protein (CRP), lactate, and bilirubin have been proposed as a diagnostic tools for appendicitis. When compared CRP, TLC and lactate are found less explicit than bilirubin as predictive markers for acute appendicitis and its complications. Objective: To determine the diagnostic accuracy of hyperbilirubinemia in diagnosing perforated appendix by taking per-operative findings as the gold standard. Material & methods: It is a cross-sectional survey conducted at the Surgery department at PAF Hospital Mushaf, Sargodha. The duration of the study was from 1st June 2018 to 1st December 2018. A total of 160 patients of both gender with acute appendicitis with Alvarado Score ≥ 7 were included. Patients with age less than 12 years, HBsAg & anti-HCV positive, history of jaundice, history of liver disease (e.g.: Crigler-Najjar, Gilbert syndrome, cirrhosis, hepatitis), the patient is alcoholic, history of hemolytic disorders (e.g.: thalassemia, spherocytosis), history of the biliary disease (e.g.: biliary stones, worm infestation, atresia, etc), history of gastrointestinal& hepato-pancreato biliary malignancy, patient with appendicular mass per-operatively and appendectomy performed incidentally or for other indications were excluded. All patients were tested by routine laboratory investigations including LFTs hyperbilirubinemia was recorded. All cases underwent appendectomy by the same surgical team& peri-operative findings were recorded & compared with pre-operative total bilirubin levels. Patients were categorized as true positive, true negative, false positive & false negative. Results: The age range in this study was from 12 to 60 years with a mean age of 35.231± 8.63 years and mean Pre-Op Bilirubin Levels was 0.812±0.72 mg/dl. Laboratory Findings (Bilirubin levels ≥ 1mg/dl) diagnosed 44(27.5%) patients and Per Operative Findings diagnosed 60(37.5%) patients with Perforated Appendix. Laboratory Findings (Bilirubin levels ≥ 1mg/dl) have shown a sensitivity of 50%, specificity of 86%, the diagnostic accuracy of 73%, PPV 68.18%, NPV 74.4%, (p=0.000) in the diagnosis of Perforated Appendix. Conclusion: It is concluded that serum bilirubin level was higher in patients with appendiceal perforation, it s a definite predictive potential in these cases. Therefore, acquiring SB values upon admission can be used in combination with more recent diagnostic tests such as CT scans n, ultrasonography to help determine the presence of perforation and thus assist in timely clinical management. Keywords: Perforated appendix, Hyperbilirubinemia, Diagnostic accuracy